The last and longest mile : Yohei Sasakawa's struggle to eliminate leprosy - Takayama, Fumihiko (Kadokawa Corporation, 2023)
The book chronicles Yohei Sasakawa's lifelong dedication to eradicating leprosy (Hansen's disease) and ending the stigma against those affected by it. It explores his global humanitarian efforts, collaboration with international health organizations, and advocacy for human rights and dignity.